Ответы и объяснения

( \sqrt[3]{m^2} + n\sqrt[3]{m} +n^2)\cdot \frac{\sqrt[3]{m^4}-\overbrace {n^3+n^2\sqrt[3]{m}}-mn }{mn^{-1}+n-n^4m^{-1}-n^2}=\\\\=((\sqrt[3]{m})^2+n\sqrt[3]{m}+n^2)\cdot  \frac{m(\sqrt[3]{m}-n)+n^2(\sqrt[3]{m}-n)}{\frac{m}{n}+n-\frac{n^4}{m}-n^2} =\\\\=(( \sqrt[3]{m})^2+n  \sqrt[3]{m}+n^2)\cdot  \frac{(\sqrt[3]{m}-n)(m+n^2))}{\frac{m^2+mn^2-n^5-mn^3}{mn}}  =\\\\=(( \sqrt[3]{m})^2+n \sqrt[3]{m}+n^2)\cdot \frac{(\sqrt[3]{m}-n)(m+n^2)\cdot mn}{m(m+n^2)-n^3(n^2+m)}=

=((\sqrt[3]{m})^2+n\sqrt[3]{m}+n^2)\cdot \frac{(\sqrt[3]{m}-n)(m+n^2)\cdot mn}{(m+n^2)(m-n^3)}=

=((\sqrt[3]{m})^2+n\sqrt[3]{m}+n^2)\cdot  \frac{(\sqrt[3]{m}-n)\cdot mn}{(\sqrt[3]{m}-n)((\sqrt[3]{m})^2+n\sqrt[3]{m}+n^2)} =mn\\\\\\P.S.\; \; a^3-b^3=(a-b)(a^2+ab+b^2)\; ,\; \; a=\sqrt[3]{m}\; ,\; b=n\; \; \to \\\\a^3-b^3=m-n^3=(\sqrt[3]{m}-n)((\sqrt[3]{m})^2+n\sqrt[3]{m}+n^2))

0.0
0 оценок
0 оценок
Оцени!
Оцени!